Pemberdayaan Perempuan Dalam Kerangka Hak Asasi Manusia - Yunita, Berliana Rahma (Eastasouth Institute, 2024)
Women's empowerment in the context of Human Rights plays a crucial role in achieving gender equality and social justice. This article aims to discuss the importance of women's empowerment as an integral part of efforts to protect basic human rights. With a human rights approach, women's empowerment is seen not only as a personal right, but also as a responsibility of the state and society to ensure equal access to education, health, work, and participation in political and social life. This article also reviews the various challenges women face in obtaining their rights, such as gender-based discrimination, violence and economic inequality. In addition, the role of international policies and institutions, such as the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW), was also discussed as an effort to support the implementation of women's rights throughout the world. Overall, women's empowerment within a human rights framework not only promotes gender equality, but also contributes to more inclusive and sustainable social, economic and political development.